Dynamical behaviour of Chiral nonlinear Schrodinger equation - Akinyemi, Lanre; İnç, Mustafa; Khater, Mostafa M. A.; Rezazadeh, Hadi (Springer, 2022)
In this work, we study the exact traveling wave solutions of (2 + 1)-dimensional Chiral nonlinear Schrodinger equation with the aid of generalized auxiliary equation method. The aforementioned model is used as a governing equation to discuss the wave in quantum field theory. The suggested technique is direct, effective, powerful, and offers constraint conditions to ensure the existence of solutions. The solutions obtained are bright solitons, dark solitons, singular solitons, mixed solitons, periodic waves, exponential, rational, and complex solutions that are relevant in various applications of applied science. Finally, some solutions are depicted in two and three dimensional to better understand the behavior of the considered model.
Keywords: Chiral nonlinear Schrodinger equation; Generalized auxiliary equation method; Soliton solutions